2/3D-QSAR, molecular docking and MD simulation studies of FtsZ protein targeting benzimidazoles derivatives. (February 2019) - Ahamad, Shahzaib; Islam, Asimul; Ahmad, Faizan; Dwivedi, Neeraj; Hassan, Md. Imtaiyaz
Abstract: The development of multi-drug and extensively-drug resistant strains of Mycobacterium tuberculosis ( Mtb ) have encouraged to develop new anti-TB agents with a unique mechanism of action. FtsZ, an essential protein of bacterial cytokinesis, has emerged as a validated target for antibacterial therapy. This study describes the utility of benzimidazoles (BI) derivatives as potential FtsZ inhibitors. Through 2/3D QSAR (MLR) molecular modeling, new BI-inhibitors with improved activity have been designed. Statistically significant models from 2D-QSAR (r 2 = 0.90, q 2 = 85 and pred_r 2 = 0.60) indicated that the descriptors such as SaaOcount, –ve Potential Surface Area, and SdsCHE-index modulate the activity of a molecule. Similarly, 3D-QSAR (r 2 = 0.78, q 2 = 0.69 and pred_r 2 = 0.59) results indicated both electrostatic and steric descriptors play a pivotal role. These indications prompted us to design 223 new BI-derivatives, out of which three BI-derivatives (D-83, D-116 andD-223 ) have shown some promising results.